2019
DOI: 10.1186/s12992-018-0447-5
|View full text |Cite
|
Sign up to set email alerts
|

Health sector fragmentation: three examples from Sierra Leone

Abstract: BackgroundFragmentation across governance structures, funding, and external actor engagement in Sierra Leone continues to challenge the efficiency and coherence of health sector activities and impedes sustained health system strengthening. Three examples are discussed to highlight the extent, causes, and impacts of health sector fragmentation in Sierra Leone: the community health worker programme, national medical supply chain, and service level agreements.ResultsIn these examples we discuss factors contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 22 publications
7
43
0
Order By: Relevance
“…This also included non-program commodities to reduce duplication and stockout and thus to strengthen efficiency of overall health systems. These findings are in line with the recommendations on systems strengthening in Sierra Leone [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This also included non-program commodities to reduce duplication and stockout and thus to strengthen efficiency of overall health systems. These findings are in line with the recommendations on systems strengthening in Sierra Leone [ 9 ].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in low- and middle-income countries documented that weak leadership and health system have led donors to establish their own planning, implementation, monitoring, accounting, and reporting mechanisms [ 6 – 8 ]. This has resulted in fragmentation of service delivery and availability of medical supplies for non-commodity programs which, in turn, led the community to high out-of-pocket (OOP) spending [ 8 , 9 , 41 ]. The consequence of financial fragmentation was that the allocated budget was not used for the priority agendas, leading to duplications and gaps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of these interventions, targeting specific diseases like hypertension, without considering structural constraints related to health systems has been debated (McCoy et al, 2005; Mills, 1983; Mounier-Jack et al, 2017; Schneider et al, 2006). Taking HIV/AIDS policies as an example, it has been shown that bypassing health systems by creating vertical structures that drain resources from a ‘crumbling core’ may address short-term needs (Schneider et al, 2006), but also contribute to health systems’ fragmentation, the duplication of services because of decontextualized donors’ priorities, the dilution and distortion of limited human and financial resources, and weak coordination between levels of care (Barr et al, 2019). The ‘health systems strengthening’ approach has been perceived as one way to improve health outcomes and the efficiency of these programs.…”
Section: Checking Persistencymentioning
confidence: 99%
“…However, these innovations are embedded in wider health system contexts that are often characterised by organisational fragmentation and siloed functioning 2–4. The ‘disarticulated state’5 is the end result of a variety of forces impacting health systems in both the global north and south: proliferation of donor aid and vertical health programmes in the Millennium Development Goal era,6 New Public Management reforms and the splitting of purchaser and provider functions,7 8 various forms of decentralisation and the growth of private (for profit and non-governmental) health sectors 4 8.…”
Section: Introductionmentioning
confidence: 99%